FAKTOR-FAKTOR HASIL PEMAHAMAN KONSEP MATEMATIS DALAM PEMBELAJARAN MASA PANDEMI COVID-19 - Adi Reza Arsiyanto; Savitri Wanabuliandari; Nur Fajrie (Jurnal Ilmiah P2M STKIP Siliwangi, 2021)
Based on the results of interviews with fourth grade students, it was stated that they did not understand mathematics because they felt mathematics was a difficult subject. Then the parents added that they couldn't guide their children to do math assignments because they didn't understand the content of the lesson. In addition, students in answering the questions given by the teacher were not optimal. Online learning is also one of the causes of the less than optimal score results. This study aims to describe the results of understanding the mathematical concepts of fourth grade students at SDN 6 Bulungcangkring during the learning period of the Covid-19 pandemic. This study used a qualitative method with research subjects, namely 3 students from grade IV SDN 6 Bulungcangkring. Data collection techniques in this study used interviews, observations, and document studies to analyze the results of students' understanding of mathematical concepts. The results of this study are that MDA is a student who is able to meet the indicators of understanding students 'mathematical concepts, while SH and JS are able to meet the indicators of understanding students' mathematical concepts because they are able to provide the right answer and are able to write formulas according to the correct calculations. The conclusion in this study is that MDA does not have the ability to understand mathematical concepts while SH and JS already have the ability to understand mathematical concepts.